Eliminating discrimination in hiring isn't enough - Mackenzie Alston (IZA World of Labor, 2023)
While many firms have recognized the importance of recruiting and hiring diverse job applicants, they should also pay attention to the challenges newly hired diverse candidates may face after entering the company. It is possible that they are being assessed by unequal or unequitable standards compared to their colleagues, and they may not have sufficient access to opportunities and resources that would benefit them. These disparities could affect the career trajectory, performance, satisfaction, and retention of minority employees. Potential solutions include randomizing task assignments and creating inclusive networking and support opportunities.
Keywords: J16; J15; J71; J28; J24; J21; 330; discrimination; gender; race; inequality; workforce diversity